2022
DOI: 10.13057/biodiv/d230215
|View full text |Cite
|
Sign up to set email alerts
|

The habitat suitability of Timor friarbird (Philemon inornatus) in Western Timor Island, Indonesia

Abstract: Abstract. Paga B, Pudyatmoko S, Wijayanti LR, Yuda P, Sulaksono N. 2021. The habitat suitability of Timor friarbird (Philemon inornatus) in Western Timor Island, Indonesia. Biodiversitas 23: 703-713. Timor friarbird is an endemic bird to Timor Island. The population of this bird has been declining due to land cover changes as a result of massive anthropogenic pressures. This study aimed to assess the suitability of Timor friarbird's habitat by using 12 ecogeographical variables. The sources of data included Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…RS technology allows for the scope of analysis to be wider spatially and temporally [200], while GIS has allowed for better spatial analyses with a combination of various watershed models. Several studies in Indonesia have used the integration of RS, GIS, and modeling for drought-prone area detection [201], habitat studies [202,203], landslide mapping [204], flood modeling [205], land use change [206], and land suitability change for specific species [207]. Modification models by integrating existing models or methods with various climate change scenarios will minimize the impacts of climate change.…”
Section: Effective Institutional and Mechanism Arrangement 631 Waters...mentioning
confidence: 99%
“…RS technology allows for the scope of analysis to be wider spatially and temporally [200], while GIS has allowed for better spatial analyses with a combination of various watershed models. Several studies in Indonesia have used the integration of RS, GIS, and modeling for drought-prone area detection [201], habitat studies [202,203], landslide mapping [204], flood modeling [205], land use change [206], and land suitability change for specific species [207]. Modification models by integrating existing models or methods with various climate change scenarios will minimize the impacts of climate change.…”
Section: Effective Institutional and Mechanism Arrangement 631 Waters...mentioning
confidence: 99%
“…This species plays an important role in forest ecosystems, agriculture, and other natural environments in the semi-arid region. Its population has decreased rapidly over the last decade, particularly in the western part of Timor Island [4,6,7]; the bird is not included in the list of protected bird species in the recent Indonesian Law (P.106 / MENLHK / SETJEN / KUM.1 / 12/2018). Previously Timor Friarbird was protected in PP No.…”
Section: Introductionmentioning
confidence: 99%
“…The studies reported that the density of the bird was very low (1 individu per two ha) [4,9]). Encounter rates in nature decreased by 82% from 2008-2011 [4] 2 continues to decline due to high anthropogenic pressure, such as habitat changes, hunting activities and wild trade of exotic and high-economic value birds [6,7]. In addition, climate fluctuations in tropical environments have intense dry seasons throughout the year, causing extreme productivity contrast in the dry and rainy seasons [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations